Parnaparin in surgery, vascular surgery and associated disciplines - D. A. lavrentyev; A. E. Zotikov («REMEDIUM GROUP» Ltd., 2020)
Aliterature review is dedicated to the use of Parnaparin in various surgical specialties. Prevention and treatment of thromboembolic complications is the major indication for the use of Parnaparin. In the review, the authors dwell on comparative studies of the efficacy oflow molecular weight heparins and unfractionated heparin. They also discuss in detail pharmacokinetics and pharmacodynamics of Parnaparin, its structure and effect on hemostasis components. Due tolack of direct comparative studies of variouslow molecular weight heparins, the authors provide reviews based on the network meta-analysis, which allowed them to identify the advantages of a specificlow molecular weight heparin by indirect comparison.There are few direct comparative studies of variouslow molecular weight heparins in theliterature, which does not allow for an objective assessment of their advantages and disadvantages. The authors do not only provideliterature data on direct comparative studies, but also show data on indirect comparisons (network meta-analysis). They analysed the efficacy of Parnaparin and otherlow molecular weight heparins for the prevention of thromboembolic complications, treatment of deep vein thrombosis and post-thrombophlebitic syndrome. The issues of the efficacy of Parnaparin in chronic arterial insufficiency and use in acute coronary syndrome are highlighted separately. The final part of the review is concerned with a promising, butlittle-known area of prophylaxis of restenosis and prevention of atherosclerosis progression. Experimental studies have allowed us to state that Parnaparin is one of the most effectivelow molecular weight heparins as far as thromboembolic complications are concerned. Parnaparin significantly reduces frequency of DVT events and, at the same time, decreases major bleeding risk as compared with unfractionated heparin. No dose adjustment is required in obese patients. Dose adjustments are based not on body weight but on risk factors for thrombosis, and obesity is only one of them to be considered to choose a dose. Amonglow molecular weight heparins, Parnaparin is one of the most potent drugs that reduces the proliferative and migratory capacity of smooth muscle cells; however, further research is needed to assess the prospects of using Parnaparin for the prevention of restenosis.